A moral kantiana entre deontologia e teleologia - Oliveira, Carlos Moisés de (2011)
This dissertation examines the Kantian moral in a teleological perspective. It consists of a reconstruction of philosophy practice that departs from the investigation of the categorical imperative, the concepts of duty, will, good will, as well as an approach on the ways of investigation of nature, which will enable the foundation to engage in the teleological argument, investigating the organized human beings, the harmonious system, its relationship with the ultimate and most important purpose, always flexing the analysis of these concepts the idea of purpose. Subsequently we will establish an argument about the end terminal and the implication of this concept to think about the real idea of the system in Kant and his relationship or support for moral theory. In essence this paper approaches the moral point of view of ethics, outlining the insufficiency of this field for the foundation of architectural moral, which will enable the final touch or the indispensability or the teleological argument as fundamental to the Kantian moral Theory